Son of cypresses : memories, reflections, and regrets from a political life - Benvenisti, Meron, 1934- (University of California Press, 2007)
''Now that I am seventy years of age, it is my prerogative to offer a summing up, '' says Meron Benvenisti, internationally known author and columnist, Jerusalem native, and scion of Israel's founders. Born in Palestine in 1934 to a Sephardic father and an Ashkenazi mother, Benvenisti has enjoyed an unusual vantage point from which to consider his homeland's conflicts and controversies. Throughout his long and provocative career as scholar, elected official, and respected journalist, he has remained intimately involved with Israel's social and political development. Part memoir and part politic.